Analisis Fundamental Komparatif dan Prospek Valuasi Saham Perbankan Big Four di Bursa Efek Indonesia Pasca-Pandemi (2021-2023) - Amrulloh, Muhammad Rizqi (Maliki Interdisciplinary Journal, 2025)
This study presents an in-depth comparative fundamental analysis of the four largest banks by market capitalization in Indonesia (the Big Four): PT Bank Central Asia Tbk (BBCA), PT Bank Rakyat Indonesia (Persero) Tbk (BBRI), PT Bank Mandiri (Persero) Tbk (BMRI), and PT Bank Negara Indonesia (Persero) Tbk (BBNI). Using secondary data from audited financial reports for the 2021-2023 period, this research applies a quantitative comparative approach to evaluate post-pandemic performance across five key dimensions: profitability, asset quality, growth, capitalization, and market valuation. The analysis reveals that while all four banks posted record net profits driven by declining provision costs, a significant challenge has emerged in the form of Net Interest Margin (NIM) compression due to rising cost of funds. BBCA demonstrates a durable competitive advantage through its superior CASA funding structure, which underpins its profitability and premium valuation. Meanwhile, BBRI excels in micro-segment credit growth, while BMRI and BBNI offer more moderate valuation profiles. This study concludes that beneath market optimism lies a significant divergence in fundamental performance, implying distinct risk-return profiles for investors.